A short note on useful codes for fluidic control circuits - Powell, E. A. (College of Aeronautics, 1968)
This note gives a survey of codes particularly useful for computational and analogue to digital circuits. Also included are logic circuits capable of converting the code into natural binary form as at some stage in a control circuit this is normally required.